Asymmetry in cerebral perfusion from circle of Willis arterial variations in normal population. Issue 1 (February 2023) - Jain, Chirag; Kumar, Ajay; Vyas, Sameer; Kumar, Ashok; Singh, Paramjeet; Bhatia, Vikas; Ahuja, Chirag; Sahu, Jitendra K; Gupta, Sunil K; Khandelwal, Niranjan
Background: Angiographic and cadaveric studies have evidenced variations in the circle of Willis (CoW). Age-related changes in cerebral hemodynamics may be attributable to vascular variations. Objectives: The objective is to assess interdependence of completeness of CoW with age using non-invasive MRA and cerebral perfusion using arterial spin labeling (ASL). Methods: This single-center, prospective study segregated 189 subjects into three groups: ≤5, 5 to 18, and >18 years. Angiographic (complete CoW and vascular asymmetry index) using TOF and contrast-enhanced- (CE-) MRA, and perfusion (perfusion asymmetry index) data using ASL were obtained. Results: One hundred and six (56.08%) subjects showed complete CoW on TOF and 100 (52.91%) on CE-MRA. Anterior and posterior collateral pathways were more prevalent in the younger population. Completeness of CoW decreased with increasing age, group 1 (54/60, 90% TOF; 51/60, 85% CE), group 2 (39/64, 60% TOF; 37/64, 56.92% CE), and group 3 (13/65, 20.31% TOF; 12/65, 18.75% CE); p-value < .0001. A statistically significant decrease in cerebral and cerebellar perfusion with increasing age was seen. Cerebellar to frontal perfusion change was higher in group 1. Fetal posterior cerebral artery (PCA) led to ipsilateral low and contralateral hyperperfusion flow asymmetries between occipital lobes. Conclusions: This study shows that a complete CoW is commoner in pediatrics than adults and with increasing age, the completeness of CoW decreases paralleled by decrease in cerebral and cerebellar perfusion. There is age-related shift of perfusion from hindbrain to forebrain and the regression of PCoA occurs with increasing age leading to alterations in cerebral perfusion and hemodynamics.